THE PROGRESS OF ISLAMIC BOARDING SCHOOL IN DEVELOPING STUDENT MORALS (Case Study in Islamic Boarding School of Darul Abrar, Bone) - Apriyani, Nur; Damopolii, Muljono; Al-Rasyid, Hamzah Harun (Jurnal Diskursus Islam, 2020)
Islamic boarding school is one of Islamic educational institution that plays an active role in the formation of human noble morals. Specifically in the development and fostering of student morals in order to form virtuous souls and understand Islamic values well. The Islamic Boarding School of Darul Abrar also plays a role in fostering the morals and mentality of the students, like boarding schools in general and also has a vision and mission to be achieved, one of which is become a person who a morality, this is in line with the ultimate goal of life. This study aims to determine the variety of morals efforts to foster student at the Islamic Boarding School of Darul Abrar, Bone. The research methodology in this study is qualitative, and the data collection techniques using observation, interviews and documentation. The results of this study indicate that efforts to develop moral character of female students can be done by increasing the reading of the Qur’an, applying disciplinary methods of discipline, applying the valuesof the five souls that are a reference to the boarding school, conducting through learning and moral guidance through extracurricular activities.